Caracterização e uso do algodoeiro no semi-árido paraaibano - Freire, Adeilson dos Santos (2017)
Gossypium hirsutum L. is one of the most useful plant species, whose fiber has multiple applications, and is responsible for most of the world textile production. Given the relevance of its importance, the study aimed to characterize the technical conditions and socio-economic aspects of the cotton production chain in producing and ex-producing localities, also evaluating the physiological quality of seeds and cotton fiber quality, aiming to contribute restructuring the cotton productive chain in the State of Paraíba/Brazil. Firstly, semi-structured interviews were conducted with farmers from producing and ex-producing localities, following a script for collecting information about the history of the cotton production, the production system and socio-economic aspects. Farmers from four production localities donated seeds and cotton bolls for evaluations, totaling 13 lots of seeds and cotton bolls (11 from farmers and 2 from CNPA / EMBRAPA). Evaluations of seeds and cotton bolls were conducted at the Laboratory of Seed Analysis (LAS) of the Federal University of Paraíba (UFPB), Areia, PB, and at the Embrapa Cotton Fiber Laboratory. Physiological seed quality evaluation consisted of the following tests and determinations: water content determination, germination test, first germination count, germination speed index, field seedling emergence, first emergency count, emergency speed index, accelerated aging, electrical conductivity and respiration. The fiber technological properties analyzed were: length, uniformity, strength, elongation at break, micronaire index, short fiber index, maturity and reliability index. The producing localities have a consolidated productive chain that needs incentives and capacity for continuity. Ex-producer locations need to restructure their production chain. Tests of accelerated aging, electrical conductivity and respiration are the most efficient in the evaluation of seed vigor and differentiation of lots. Lots of Gurinhém farmers have the greatest vigor of seeds and quality of fibers, lots of Juarez Távora and Remígio farmers presented the lower vigor and fiber quality.